2012
DOI: 10.1016/j.ejpain.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gonadal steroid hormones on formalin‐induced temporomandibular joint inflammation

Abstract: We have recently demonstrated that gonadal steroid hormones decrease formalin-induced temporomandibular joint nociception in rats. Given that the attenuation of inflammation is a potential mechanism underlying this antinociceptive effect, we evaluated the effect of gonadal steroid hormones on formalin-induced temporomandibular joint inflammation. Plasma extravasation, a major sign of acute inflammation, and neutrophil migration, an important event related to tissue injury, were evaluated. Formalin induced sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 60 publications
2
23
1
4
Order By: Relevance
“…It is well established that estrogen displays analgesic properties in animal models of inflammatory pain and that estrogen antiinflammatory and antinociceptive effects have been postulated to be in part mediated through down regulation of inflammatory modulators [23,4749]. Here we analyzed the cytokine profile during estradiol administration before and following formalin injection and observed that estrogen directly regulates pro- and antiinflammatory cytokine levels in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that estrogen displays analgesic properties in animal models of inflammatory pain and that estrogen antiinflammatory and antinociceptive effects have been postulated to be in part mediated through down regulation of inflammatory modulators [23,4749]. Here we analyzed the cytokine profile during estradiol administration before and following formalin injection and observed that estrogen directly regulates pro- and antiinflammatory cytokine levels in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…The optical density was read at 450 nm using an Asys UVM340. After that, the results were calculated by comparing the optical density of rat’s knee joint synovial lavage fluid supernatant with a standard curve of neutrophil (>95% purity), as previously described [43]. The results were presented as number of neutrophils × 10 4 /knee.…”
Section: Methodsmentioning
confidence: 99%
“…The myeloperoxidase kinetic-colorimetric assay was used, as previously described (Torres-Chavez et al, 2012). Three hours after injection, the tissue of the plantar surface of the hind paw was dissected into a standard sized sample, weighed, quickly frozen by liquid isopentane in dry ice and stored at À70 C. In the assay procedure, each sample was homogenized in 500 ml of buffer 1 (0.1 M NaCl, 0.02 M NaPO 4 , 1.015 M Na EDTA, pH 4.7) followed by centrifugation at 3000 rpm for 15 min.…”
Section: Measurement Of Myeloperoxidase Activitymentioning
confidence: 99%
“…The optical density was read at 450 nm using an Anthos 2020. Results were calculated by comparing the optical density of hind paw tissue supernatant with a standard curve of neutrophil (>95% purity) obtained as previously described (Torres-Chavez et al, 2012). The results were presented as number of neutrophils Â10 6 /mg tissue.…”
Section: Measurement Of Myeloperoxidase Activitymentioning
confidence: 99%